Legal Protection For Consumers In Unilateral Concert Cancellations (Case Study Of The Ndx Band Concert In Palangkaraya: Bajenta Fest 2024 Event) - Dani Lailatul Magviro; R.Anisatul Mukaromah M; Yasid Amali; Kholis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The entertainment industry, particularly music concerts, has become one of the most popular forms of entertainment among the public. However, in practice, unilateral concert cancellations by organizers often occur and potentially harm consumers as ticket buyers. This research aims to analyze the legal protection provided to consumers in cases of unilateral concert cancellations, using the case study of the NDX Band concert at the Bajenta Fest 2024 event, which was abruptly canceled by the organizer without clear accountability. This study employs a normative juridical method using statutory, conceptual, and case approaches. The data used are secondary data consisting of primary, secondary, and tertiary legal materials. The data analysis is conducted qualitatively by reviewing applicable positive legal norms, such as Law Number 8 of 1999 concerning Consumer Protection, the Indonesian Civil Code (KUHPer), and legal doctrines related to business actors’ liability. The findings indicate that the unilateral cancellation of a concert constitutes a breach of contract, thereby obligating the business actor to provide compensation, restitution, and/or ticket refunds in accordance with Article 4 point (h) and Article 7 point (g) of the Consumer Protection Law. Moreover, the delayed refund process lasting several months without legal certainty demonstrates the weak enforcement of consumer protection in the entertainment sector. Therefore, strengthening regulations and supervisory mechanisms over business actors in the entertainment industry is necessary to ensure the effective protection of consumer rights.